Field notes contributed by Hank Zaletel, spring 1982 - Zaletel, Hanket al (1982)
Field notes were contributed by Hank Zaletel. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1982. Epson - sheet feed